Chemical characteristics of organic wastes and their potential use for acid mine drainage remediation - Munawar, Ali; Riwandi, Riwandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Organic substrate is an important component of biological treatments for acid mine drainage (AMD) remediation systems. It provides organic substrates to sulfate-reducing bacteria (SRB) in the sulfate (SO4) reduction, resulting in increased alkalinity and metal sulfide precipitates. Natural organic matters vary in their characteristics, and therefore may perform differently for remediation properties. This study was aimed to characterize four locally available organic wastes (bark, empty fruit bunch, sawdust, and chicken manure) potential for AMD remediation. Their chemical properties and elemental compositions were measured. An anaerobic incubation of these wastes in AMD was undertaken to determine their remediation properties. The pH, electrical conductivity (EC), redox potential (Eh), and dissolved Fe and SO4 of the mixtures were measured after the 1st, 7th, 14th, and 30th day of the incubation at room temperature. The results demonstrated that organic wastes varied in their chemical properties and performed differently in treating AMD. Organic wastes containing high alkalinity (high pH) and nutrient concentrations (chicken manure and empty fruit bunch) improved AMD quality through increasing pH (>6) and reducing dissolved Fe and SO4 concentrations. Although sawdust and bark (high CEC) did not increase pH up to acceptable standard at most time, they apparently were able to remove dissolved Fe from AMD through adsorption mechanism.